2018
DOI: 10.1007/s10006-018-0686-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasonic scalpel and monopolar electrocautery for skin incisions in neck dissection: a prospective randomized trial

Abstract: UC results in less postoperative pain and less bleeding in the neck incision area. Accordingly, UC is superior to ME for skin incisions in neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…An ultrasonic knife is very convenient to carry out separation of tissues and pathologically altered structures from normal ones, which is expedient for scars' excision. In a randomized trial, Schneider D et al performed an intraoperative and postoperative comparison of wounds -incisions applied to skin in neck dissection using an ultrasound scalpel (15 patients) and a monopolar electrocautery (15 patients), which were standard equipment for soft tissue surgery [5]. It is shown that ultrasonic scalpel led to a decrease in bleeding in the incision and postoperative pain, while the operation time and complications in both groups were the same.…”
Section: Resultsmentioning
confidence: 99%
“…An ultrasonic knife is very convenient to carry out separation of tissues and pathologically altered structures from normal ones, which is expedient for scars' excision. In a randomized trial, Schneider D et al performed an intraoperative and postoperative comparison of wounds -incisions applied to skin in neck dissection using an ultrasound scalpel (15 patients) and a monopolar electrocautery (15 patients), which were standard equipment for soft tissue surgery [5]. It is shown that ultrasonic scalpel led to a decrease in bleeding in the incision and postoperative pain, while the operation time and complications in both groups were the same.…”
Section: Resultsmentioning
confidence: 99%
“…These investigations utilise an application-specific transducer and blade construction. The use of ultrasonic cutting has also been investigated in the support of surgeries [6,7,8]. However, the key consideration in these investigations was the effect of temperature where a lower temperature rise resulted in less tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Use of this device can lead to reduced lateral thermal spread and adjacent tissue destruction, 15,16 contributing to reduced postoperative pain and less bleeding in the surgical area. 17 This study was performed to compare the oncologic outcomes, surgical variables, complications, and functional results of TGE and harmonic scalpel-assisted MECD (HS-MECD), which is an advanced technique in the management of benign tumours of the SMG. Hypothetically, because HS-MECD is less invasive, this new approach may lead to fewer complications and improved outcomes without increasing the incidence of recurrence.…”
Section: Introductionmentioning
confidence: 99%